Use of radon-222 to assess the groundwater inflow in a phreatic lake of a dune field (San Luis, Argentine) - Echegoyen, Cecilia Vanina (2021)
In the southeastern portion of San Luis Province (33°53’10’’-34°19’00’’ S and 65°42’00’’-65°20’00’’ W), the sand dune landscape hosts a lacustrine system with more than 200 water bodies, where the water table reaches the surface and fills the deepest depressions. The aim of this study is to analyze surface-groundwater interactions using the radioactive isotope radon-222 (222Rn) in a lake known as “Los Pocitos”. During September 2017, in situ222Rn determinations were performed in the air; in the water/sediment interface and in surface waters at 6 sampling stations, as well as in 4 groundwater samples collected in the dune and the lake mudflat using the RAD-7 equipment (Durridge Co.). Surface waters are of the HCO3--Na+-K+ type, with mean pH and electrical conductivity in Lake Los Pocitos of 8.7 and 1232 µS cm-1, respectively, whereas the groundwater is of the HCO3--Ca+2 type, with variable pH and electrical conductivity values. In the northern portion of the lake, concentrations of222Rn in surface water were ~ 70 Bq m-3, one order of magnitude greater than those of the southern sector, which registered values < 5 Bq m-3. By means of a222Rn mass balance model it was possible to determine that the groundwater discharge occurs in the northern sector, with an inflow discharge rate of about 185.3 ± 39.1 m3 d-1, whereas in the southern sector, an outflow from the lake to the surrounding aqui-fers can be detected. The intense groundwater inflow into these lakes may explain their relatively low salinity under a semi-arid climate in which evaporation by far exceeds direct rainfall input.